Growing Innovation and Creativity of Nusantara KKN Students in Trauma Healing in Mangga Tree Hamlet, Salahutu, Central Maluku - Muhammad Permadi (Transformatif : Jurnal Pengabdian Masyarakat, 2020)
This article reveals the innovation and creativity of KKN Nusantara 3T students in trauma healing in the Dusun Pohon Mangga.At the Tulehu Pohon Mangga before the disaster struck, the mentality of the community itself was afraid and worried over the earthquake that hit their village. The innovation and creativity of the Nusantara KKN students is to provide educational assistance to the community (Trauma Healing) which has an impact on the earthquake, so that the community no longer experiences prolonged trauma. The result of this research is that through the form of a work program carried out, the Trauma healing that is presented is able to restore the community from various backgrounds, ranging from children, adolescents and youth, to adults.During the 3T Nusantara Community Service in Dusun Pohon Mangga, the earthquake trauma recovery manifested through various activities and work programs was carried out well. KKN students have successfully overcome various problems and obstacles during KKN, both internal and external. Various problems and obstacles can be controlled and resolved with strategic and solution steps armed with the knowledge on campus and the experience of each student.